PENGARUH PENAMBAHAN ABU TERBANG BATU BARA DAN PUPUK KANDANG AYAM TERHADAP SERAPAN P DAN PERTUMBUHAN TANAMAN JAGUNG PADA ULTISOL - Muhammad Miftakhul Falah; Reni Ustiatik; Yulia Nuraini (Departemen Tanah, Fakultas Pertanian, Universitas Brawijaya, 2023)
Maize is one of the world's food crops besides wheat and rice, which is strategic to increase production. Ultisol is a type of soil spread across Indonesia with a land area distribution of 45,794,000 ha and has the potential to be used to increase corn crop production. This study aimed to elucidate the effect of the combination of coal fly ash (CFA) and chicken manure (CM) on P uptake and growth of maize grown on an Ultisol. The CFA doses applied were 0, 10 and 20 t ha-1 of coal fly ash, while the CM doses applied were 0, 10 and 20 t ha-1 of chicken manure. Observations included soil pH, total P, available P and P uptake by maize. The results of the study showed an increase in soil pH, but still showed a value below 5,5. The addition of coal fly ash and chicken manure as much as 20 t ha-1 provided the highest P availability and showed the highest P nutrient uptake value by corn crops. The application of coal fly ash and chicken manure can increase the availability of P better than without the addition of chicken manure. But, the application of coal fly ash up to 20 t ha-1 also inhibited the growth of maize by marking a decrease in the results of measuring the dry weight and height of maize plants.